Statement of Contribution to Diversity, Equity, and Inclusion for JGR: Biogeosciences. Issue 2 (27th January 2022) - Xenopoulos, Marguerite A.; Desai, Ankur; Huntzinger, Deborah; Bastos, Ana; Fawcett, Sarah; Sahagian, Dork; Santin, Cristina; Vargas, Rodrigo
Abstract: Here we are presenting a statement of Diversity, Equity and Inclusion (DEI) for JGR: Biogeosciences . This statement includes current policies and practices, and details concrete actions that we intend to implement over the next year to better include underrepresented groups in the publication process. Key Points: The impact of our journal is enhanced when a representative pool of contributors participates in the process of scientific publication Increasing reviewer and editor diversity is the best opportunity we have to remove bias from the peer review process Key priorities to expand and diversify our editorial, reviewing, and publishing community are highlighted